Economic and productive analysis of irrigated rice crops using a multicase study - Xavier, Arthur Inácio Saldanha; Arbage, Alessandro Porporatti; Silva, Michel Rocha da; Ribas, Giovana Ghisleni; Meus, Lorenzo Dalcin; Santos, Gionei Alves de Assis dos; Streck, Nereu Augusto; Zanon, Alencar Junior (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the relationship between grain yield and production costs of flood-irrigated rice (Oryza sativa) in the state of Rio Grande do Sul, Brazil, in order to determine the yield range that maximizes the profit of farmers. There are estimations pointing out that the yield range that maximizes the profit for farmers is about 75 and 85% of the yield potential; however, this still needs to be validated for irrigated rice in Brazil. To validate these values, a technical and economic monitoring was carried out for eight farmers of irrigated rice, whose production costs were measured and compared with the mean yield and the percentage of potential yield achieved. To determine the potential yield of each crop, SimulArroz, a process-based model developed for the simulation of rice growth and yield in the South of Brazil, was used. The grain yield achieved by the farmers ranged from 6.3 to 11.0 Mg ha-1 (48 to 83% of the potential yield), costs ranged from R4,197.00 ha-1 to R6,227.00 ha-1, and profit ranged from R-52.00 ha-1 to R3,599.00 ha-1. Farmers who reach between 69 and 83% of yield potential achieve the highest profitability. The investment planning based on the yield potential calculated by the SimulArroz model can be efficiently adopted for irrigated rice crops.